2016
DOI: 10.1007/s11999-015-4602-5
|View full text |Cite
|
Sign up to set email alerts
|

What Are the 30-day Readmission Rates Across Orthopaedic Subspecialties?

Abstract: Background The Centers for Medicare & Medicaid Services (CMS) now include hip and knee replacements in the Hospital Readmission Reduction Program. The 30-day readmission rate is an important quality metric; however, the incidence has not yet been defined across the numerous orthopaedic subspecialties. Elucidating the readmission rate for each subspecialty may indicate that certain services are being disincentivized by the CMS reimbursement program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…20 Moreover, 30-day readmissions for other specialties are significantly higher, with rates for internal medicine and general surgery reported at 12 to 14% and 11 to 12%, respectively. 32,33 The data presented here from our institution demonstrate a 90-day readmission rate of 4.86% (79/1,625), with a 3.2% (52/1,625) 30-day readmission rate following elective TKA. These are comparable with other studies reporting 4 to 9% 90-day readmission rates and a NSQIP database review suggesting 30-day readmission rates between 4 and 6%.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…20 Moreover, 30-day readmissions for other specialties are significantly higher, with rates for internal medicine and general surgery reported at 12 to 14% and 11 to 12%, respectively. 32,33 The data presented here from our institution demonstrate a 90-day readmission rate of 4.86% (79/1,625), with a 3.2% (52/1,625) 30-day readmission rate following elective TKA. These are comparable with other studies reporting 4 to 9% 90-day readmission rates and a NSQIP database review suggesting 30-day readmission rates between 4 and 6%.…”
Section: Discussionmentioning
confidence: 72%
“…These are comparable with other studies reporting 4 to 9% 90-day readmission rates and a NSQIP database review suggesting 30-day readmission rates between 4 and 6%. 28,[33][34][35] Readmissions within 30 days are considered an important quality metric by CMS making it an appropriate target for surgeons and health care systems to evaluate. 33 Roughly two-thirds (52/79) of medical and orthopaedic readmissions in our study occurred within 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general orthopedic population is operatively diverse, encompassing everything from trauma to TJA and spine services. However, 30‐day readmission rates are relatively similar between the subspecialties, at approximately 3% to 6% for all‐cause readmissions 7‐11 . The most common reasons for readmission across the orthopedic patient population are infection, cardiopulmonary disease, and procedure/device complication 12‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…The most common reasons for readmission across the orthopedic patient population are infection, cardiopulmonary disease, and procedure/device complication 12‐14 . Previous studies have identified increased American Society of Anesthesiologists (ASA) class, smoking, diabetes, insurance status, sex, Charlson Comorbidity Index (CCI) score, and extended length of stay (LOS) as being predictive of readmission risk 8,10,11,13 . These variables represent the large pool of patient data that can be leveraged for readmission prediction, but currently, there is no definitive tool to facilitate the integration of this array of risk factors.…”
Section: Introductionmentioning
confidence: 99%